Combined molecular characterization and dopa-responsive treatment in two patients with NR4A2-associated intellectual developmental disorder - Liang, Na; Li, Ting; Deng, Yang (Frontiers in Genetics, 2025)
IntroductionPathogenic variants in NR4A2 are associated with neurodevelopmental disorders including intellectual developmental disorder with language impairment and early-onset dopa-responsive dystonia-parkinsonism (IDLDP). Here we report two pediatric NR4A2-related cases presenting with global developmental delay, speech impairment, and intellectual disability.MethodsComprehensive genetic investigations including whole-exome sequencing revealed a de novo missense variant (c.994G>C, p.Val332Leu) in NR4A2 and a 2q23.3-q24.2 deletion encompassing NR4A2. Functional validation via RNA sequencing revealed that the missense variant induces pathogenic exon 4 skipping through aberrant splicing. Both patients exhibited marked clinical improvements in linguistic competence and motor function following levodopa therapy, initiated after confirmation of dopaminergic responsiveness. A systematic review of 19 reported NR4A2-related cases revealed substantial phenotypic heterogeneity, with three of them demonstrating favorable responses to dopaminergic treatment.ResultsOur findings underscore the diagnostic value of integrating molecular profiling with functional RNA analysis to resolve complex neurogenetic disorders. Levodopa therapy shows therapeutic potential for NR4A2-deficient patients with dopa-responsive features, especially in linguistic improvement. This study expands the understanding of NR4A2-associated pathogenesis and provides insights for the precision management of related neurodevelopmental conditions.